2019 IEEE/CVF Conference on Computer Vision and Pattern Recognition (CVPR) 2019
DOI: 10.1109/cvpr.2019.00994
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric Capture of Humans With a Single RGBD Camera via Semi-Parametric Learning

Abstract: Volumetric (4D) performance capture is fundamental for AR/VR content generation. Whereas previous work in 4D performance capture has shown impressive results in studio settings, the technology is still far from being accessible to a typical consumer who, at best, might own a single RGBD sensor. Thus, in this work, we propose a method to synthesize free viewpoint renderings using a single RGBD camera.The key insight is to leverage previously seen "calibration" images of a given user to extrapolate what should b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…Most recent techniques or generating real-time volumetric avatars are focusing on learning-based approaches. By leveraging neural rendering techniques these novel methods have achieved unprecedented results, enabling the modeling of view-dependent effects such as specularity and also correcting for imperfect geometry (Lombardi et al, 2018(Lombardi et al, , 2019Pandey et al, 2019). Compared to traditional graphics pipelines, these new methods require less computation and also can deal with a coarser geometry, which is usually used as a proxy for rendering the final 3D model.…”
Section: Volumetric Avatarsmentioning
confidence: 99%
“…Most recent techniques or generating real-time volumetric avatars are focusing on learning-based approaches. By leveraging neural rendering techniques these novel methods have achieved unprecedented results, enabling the modeling of view-dependent effects such as specularity and also correcting for imperfect geometry (Lombardi et al, 2018(Lombardi et al, , 2019Pandey et al, 2019). Compared to traditional graphics pipelines, these new methods require less computation and also can deal with a coarser geometry, which is usually used as a proxy for rendering the final 3D model.…”
Section: Volumetric Avatarsmentioning
confidence: 99%
“…Machine Learning. Very recent advances in deep learning have enabled realistic synthesis of humans [Balakrishnan et al 2018;Chan et al 2018;Ma et al 2017Ma et al , 2018Neverova et al 2018;Pandey et al 2019;Si et al 2018;Zhao et al 2017]. Zhao et al [2017] use coarse-tofine Generative Adversarial Networks (GANs) to synthesize images that are still relatively blurry.…”
Section: Related Workmentioning
confidence: 99%
“…The very recent work of Pandey et al [2019] showed how to disentangle appearance, pose, and viewpoint, generating compelling renderings from arbitrary views using just a single sensor. In Lombardi et al [2019] authors provide an elegant solution to combine mesh based rendering with neural rendering by learning a 3D volume representation from multiple RGB images.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, wavelet transform is helpful for 3D-image coding and compression, and improves the quality of data transmission. Pandey et al [7] propose a virtual view synthesis method using a single Red-Green-Blue-Depth (RGBD) camera. It can generate novel renderings of the performer based on the past observations from multiple viewpoints and the current RGBD image from a fixed view.…”
Section: Introductionmentioning
confidence: 99%